SR-Related Protein TAXREB803/SRL300 Is an Important Cellular Factor for the Transactivational Function of Human T-Cell Lymphotropic Virus Type 1 Tax - Youn, Hwang-Geum (American Society for Microbiology, 2003)
Expression of the human T-cell lymphotropic virus type 1 (HTLV-1) genes is transcriptionally activated by the cognate oncoprotein Tax which enhances the binding of the cyclin AMP-responsive element binding protein (CREB) to the Tax responsive element (TxRE) located in its long terminal repeat (LTR). TxRE is highly homologous to the cyclic AMP-responsive element (CRE) except for the GC-rich sequence flanking the CRE. We cloned the cDNA for a cellular factor, TAXREB803, of which the DNA-binding domain bound to TxRE and the binding was dependent on the 3′ GC-rich sequence in TxRE. TAXREB803 is an SR-related protein composed of 2,752 amino acids including numerous arginine/serine (RS) motifs. TAXREB803 enhanced both the Tax dependent transcription and the CREB binding to TxRE in cooperation with Tax. The interaction of TAXREB803 and Tax was detected by coimmunoprecipitation assays as well as by indirect immunofluorescence assays. Significantly, Tax transactivation for the HTLV-1 LTR decreased dramatically when the expression level of the endogenous TAXREB803 was suppressed by the small interfering RNA. These results suggest that TAXREB803 functions as a transcriptional coactivator for Tax and plays a critical role in the expression of HTLV-1 genes.